The peak of blood lactate during the first 24 h predicts mortality in acute coronary syndrome patients under extracorporeal membrane oxygenation. (15th October 2016) - Rigamonti, Fabio; Montecucco, Fabrizio; Boroli, Filippo; Rey, Florian; Gencer, Baris; Cikirikcioglu, Mustafa; Reverdin, Stéphane; Carbone, Federico; Noble, Stephane; Roffi, Marco; Banfi, Carlo; Giraud, Raphael
Abstract: Background: Parameters allowing for outcome discrimination of extracorporeal membrane oxygenation (ECMO) therapy in acute coronary syndromes (ACS) complicated by refractory cardiogenic shock (CS) and/or cardio-respiratory arrest (CA) remain elusive. We aimed at evaluating the potential prognostic roles of blood and procedural parameters associated with 30-day mortality following ECMO. Methods and results: A group of 29 patients with ACS complicated by CS and/or CA, who underwent ECMO at a single center, was retrospectively analyzed. Eighteen patients (62%) died at 30-day follow up. "Survivors" and "non-survivors" had similar demographics, clinical and biochemical characteristics at admission, except for blood lactate peak in the first 24 h that was increased in non-survivors. Procedural characteristics of percutaneous coronary intervention (PCI) and ECMO were comparable in either group. The peak of blood lactate concentration predicted 30-day mortality independently of age, sex and ECMO duration. The cutoff value, determined by receiver operating characteristic (ROC) curve analysis, was found at 11 mmol/l. Conclusions: The peak of serum lactate under ECMO in the first 24 h predicted 30-day mortality in patients with ACS complicated with CS and CA.